Synthesis of Hydroxyapatite Coatings with Hexagonal Crystal Structure on Etched Titanium by Hydrothermal Method - Thong, Nguyen Huu; Hue, Bui Thi; Duong, Le Quynh; Toan, Le Van; Van, Hoang Nhu; Tung, Duong Thanh; Thang, Cao Xuan; Tung, Nguyen Viet; Lan, Nguyen Thi; Vuong, Hoang Van; Hung, Le Thai; Vuong, Pham Hung (VNU Journal of Science: Mathematics - Physics, 2022)
Hydroxyapatite (HAp) has been successfully coated on etched titanium substrates by hydrothermal method using solutions of Ca(NO 3 ) 2 .4H 2 O, NH 4 H 2 PO 4 at 200 o C for 12 h. Results obtained from measurements on the modern physical methods of FE-SEM and XRD showedhat the structure of HAp has a regular hexagonal morphology belonging to the space group P63/m. The degree of HAp nucleation and nucleation development on the un-etched titanium plates was lower than that on the etched titanium plates. In vitro bioactivity of HAp-coated titanium testing using SBF solution showed prospective results. Keywords: Hydroxyapatite (HAp), Hydrothermal method, etched, titanium.